2009
DOI: 10.1038/jhh.2008.166
|View full text |Cite
|
Sign up to set email alerts
|

Trends in high blood pressure prevalence in Greek adolescents

Abstract: A school-based screening with anthropometric and blood pressure (BP) measurements was performed in adolescents aged 12-17 years in the island of Samos, . In multivariate analysis, BMI, male gender and age, but also modifiable factors (lack of physical activity, breakfast skipping, smoking and low milk consumption) were associated with increased BP levels in the study population. These data indicate that further to BMI, other factors such as adverse lifestyle and dietary habits appear to be associated with elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 30 publications
5
57
1
5
Order By: Relevance
“…7 The trends in the mean BP and the prevalence of hypertension are similar to some of these studies. 7,8,14,15,22 In the United States, the Princeton School Study demonstrated that both the mean SBP and DBP were significantly higher in 1973-1975, than 1989-1990 among children aged 7-12 (Morrison et al 22 ). Between the US NHANES III (1988)(1989)(1990)(1991)(1992)(1993)(1994) and the NHANES (1999-2000) surveys, the mean BP and the prevalence of hypertension also increased among both genders between the ages of 8 and 17 (Muntner et al 14 ; Din-Dzietham et al 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7 The trends in the mean BP and the prevalence of hypertension are similar to some of these studies. 7,8,14,15,22 In the United States, the Princeton School Study demonstrated that both the mean SBP and DBP were significantly higher in 1973-1975, than 1989-1990 among children aged 7-12 (Morrison et al 22 ). Between the US NHANES III (1988)(1989)(1990)(1991)(1992)(1993)(1994) and the NHANES (1999-2000) surveys, the mean BP and the prevalence of hypertension also increased among both genders between the ages of 8 and 17 (Muntner et al 14 ; Din-Dzietham et al 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…7,8,14,15,22,34,35 Past studies reported that over the past decade, the prevalence of hypertension remains stable or decreases in economically developed countries, however, it increases in developing countries. 3 Taiwan, an economically developed country, also experienced a decrease in the prevalence of hypertension (age-adjusted prevalence: 26.6-23.5%, from 1993 to 2002) and a decrease in the mean BP in adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] This change may have important implications in terms of future cardiovascular risk as increased BP levels during childhood predict hypertension in adolescence and early adulthood [4][5][6][7] and are associated with the presence of target-organ damage. [8][9][10][11][12][13] As it is the case in adults, the phenomena of white-coat and masked hypertension appear to be common in young individuals.…”
Section: Introductionmentioning
confidence: 99%